Thermodynamic stability and flexibility characteristics of antibody fragment complexes - Li, Tong (Protein Pept Lett, 2014)
Free energy landscapes, backbone flexibility and residue-residue couplings for being co-rigid or co-flexible are calculated from the minimal Distance Constraint Model (mDCM) on an exploratory dataset consisting of VL, scFv and Fab antibody fragments. Experimental heat capacity curves are reproduced markedly well, and an analysis of quantitative stability/flexibility relationships (QSFR) is applied to a representative VL domain and several complexes in the scFv and Fab forms. Global flexibility in the denatured ensemble typically decreases in the larger complexes due to domain-domain interfaces. Slight decreases in global flexibility also occur in the native state of the larger fragments, but with a concurrent large increase in correlated flexibility. Typically, a VL fragment has more co-rigid residue pairs when isolated compared to the scFv and Fab forms, where correlated flexibility appears upon complex formation. This context dependence on residue-residue couplings in the VL domain across length scales of a complex is consistent with the evolutionary hypothesis of antibody maturation. In comparing two scFv mutants with similar thermodynamic stability, local and long-ranged changes in backbone flexibility are observed. In the case of anti-p24 HIV-1 Fab, a variety of QSFR metrics were found to be atypical, which includes comparatively greater co-flexibility in the VH domain and less co-flexibility in the VL domain. Interestingly, this fragment is the only example of a polyspecific antibody in our dataset. Finally, the mDCM method is extended to cases where thermodynamic data is incomplete, enabling high throughput QSFR studies on large numbers of antibody fragments and their complexes.